# 2+square root of 4-x=x

rewrite it as

√(4-x) = x-2

now square both sides

4-x = x^2 - 4x + 4

x(x-3)=0

so x = 0 or x = 3

**BUT** when we square an equation, all answers must be verified in the original equation

Which answer works and which doesn't?

## To verify which answer works and which doesn't, we need to substitute both values of x (0 and 3) back into the original equation:

For x = 0:

2 + √(4 - 0) = 0

2 + √4 = 0

2 + 2 = 0

4 = 0

This equation is not true, so x = 0 is not a valid solution.

For x = 3:

2 + √(4 - 3) = 3

2 + √1 = 3

2 + 1 = 3

3 = 3

This equation is true, so x = 3 is a valid solution.

Therefore, the only solution that works is x = 3.